The association of sleep quality and aggression: A systematic review and meta-analysis of observational studies. (October 2021) - Van Veen, Maaike M.; Lancel, Marike; Beijer, Elise; Remmelzwaal, Sharon; Rutters, Femke
Summary: Poor sleep quality is closely related to aggression, but despite the promise of new therapeutic possibilities, a systematic synthesis of observational research on the association between sleep quality and aggression is lacking. This systematic review and meta-analysis examined the association between sleep quality and aggression, using the academic databases PubMed and PsycINFO. Subjective and objective measures of sleep quality were included, as well as multiple measures of aggression, assessing aggressive and externalizing behavior, anger, hostility and irritability. Ninety-two observational articles, containing 96 studies, encompassing a total of 58.154 children, adolescents and adults were sourced out of 7161 references identified. Methodological quality was moderate or strong in 76% of studies. Data for meta-analysis was available from 74 studies. Poorer sleep quality was associated with higher aggression in 80.8% of studies. Pooled results showed a correlation of 0.28 (95%CI 0.25–0.31; I 2  = 90.1%) and odds ratio of 3.61 (95%CI 1.13–11.51; I 2  = 88.3%). Effect estimates and heterogeneity varied according to population type and measurement instruments, but not according to article quality or age group. Our findings confirm that poor sleep quality is consistently associated with higher aggression. As most evidence is cross-sectional, more prospective and high-quality experimental evidence is required to elucidate cause-effect and optimize prevention and treatment of aggression.